Health-promoting lifestyles and related factors among pregnant women/Gebelerde sağlıklı yaşam biçimi davranışları ve ilişkili faktörler - Güliz Onat; Yılda Arzu Aba (Turkish Society of Public Health Specialists, 2014)
Abstract Objective: A health-promoting lifestyle has an especially important role during pregnancy due to its direct link to healthy births, and to low maternal-fetal mortality and morbidity rates. The objectives of our study are to determine and analyse the health-promoting lifestyles and related factors in pregnant women. Methods: This descriptive study was carried out on 255 pregnant women in the city of Usak in Turkey, using the Health-Promoting-Lifestyle-Profile-II-(HPLP). Frequencies, percentage distributions, t tests, and the Mann Whitney U test and ANOVA were used to analyze the results. Results: The mean age of the pregnant women was 26.7±5.1 and their mean gestational week was 25.2±10.9. The mean total score on the HPLP was 130.7±20.0. The lowest score was for "physical activity" (14.4±5.0). The highest score was for "psychological wellbeing" (26.18±4.2). Smoking prevalence among the study population was 17% before the pregnancy,  and 3.9% during the pregnancy (with an average of 4 cigarettes/day). During the pregnancy diet habits improved. The rate of giving up smoking was high. Women also sought further knowledge about pregnancy and birth. Conclusions: In pregnant women the HPLP score was upper to intermediate in level. Of the women who participated in the survey, those that were unemployed, had a lower level of education, and those who had considered abortion were found to be at a higher risk of not having a health promoting life style. This finding provides a unique insight in identifying the risk group for health care providers who work at an antenatal clinic. Health caregivers should pay more attention to this risk group when evaluating healthy lifestyles during whole pregnancy. Key Words: Health-Promoting Lifestyles; pregnant women; Health Promoting Lifestyle Profile-II Özet Amaç: Sağlıklı yaşam biçimi davranışları; sağlıklı ve canlı bir doğum yapma, anne-yenidoğan mortalite ve morbidite oranını azaltma açısından özellikle gebelik sürecinde oldukça önemlidir. Bu çalışmada gebe kadınlaın sağlıklı yaşam biçimi davranışları ve ilişkili faktörlerinin araştırılması amaçlanmıştır. Yöntem: Tanımlayıcı nitelikte olan bu çalışma, Uşak'ta 255 gebe kadın üzerinde gerçekleşmiştir. Çalışmada Sağlıklı Yaşam Biçimi Davranışları Ölçeği-II (SYBDÖ-II) kullanılmıştır. İstatistiksel değerlendirmede sıklık ve yüzdelik dağılım, t test, Mann Whitney U test and ANOVA kullanılmıştır. Bulgular:Kadınların yaş ortalaması 26.7±5.1 ve gestasyonel yaşı 25.2±10.9 haftadır. Toplam SYBDÖ-II puanı 130.7.±20.0 idi. Ölçeğe ait en düşük puan "fiziksel aktivite" alt grubuna, (14.4±5.0) en yüksek puan ise "manevi gelişim" e aittir (26.1±4.2). Gebelik öncesi sigara içme sıklığı %16.9 iken, gebelikte bu oran %3.9'dur (ortalama 4 sigara/gün).  Kadınların gebelikte beslenme alışkanlıkları iyileşmiştir; öte yandan halen sigara içen gebeler bulunmaktadır ve fiziksel aktivitelerindeki değişimler yetersizdir. Ayrıca kadınlar gebelik ve doğum hakkında bilgi alma gereksinimindedir. Sonuç: Gebe kadınlarda SYBDÖ-II puanı üst-orta seviyededir. Eğitim seviyesi düşük, işsiz ve gebeliğini sonlandırmak isteyen kadınların, sağlıksız davranışlar açısından risk grubunda olduğu belirlenmiştir. Bu bulgular, doğum öncesi kliniklerde çalışan sağlık personeline riskli grubu belirleme açısından ipuçları sunar. Sağlık bakımı sunanların, sağlıklı yaşam biçimi davranışları açısından belirlenen riskli grubu daha dikkatli değerlendirilmesi önerilmektedir. Anahtar Kelimeler: Sağlıklı Yaşam Biçimi Davranışları; gebe kadınlar; Sağlıklı Yaşam Biçimi Davranışları Ölçeği-II